Health Optimization Program for Elders: Improving the Transition From Hospital to Skilled Nursing Facility. Issue 3 (July 2019) - Krol, Michael L.; Allen, Colette; Matters, Loretta; Jolly Graham, Aubrey; English, William; White, Heidi K.
Abstract : Background: Individuals discharged from the hospital to skilled nursing facilities (SNFs) experience high rates of unplanned hospital readmission, indicating opportunity for improvement in transitional care. Local Problem: Local physicians providing care in SNFs were not associated with the discharging hospital health care system. As a result, substantive real-time communication between hospital and SNF physicians was not occurring. Methods: A multidisciplinary team developed and monitored implementation of the Health Optimization Program for Elders (HOPE) to improve patient transitions from acute hospital stay to SNFs. Interventions: The HOPE used a nurse practitioner (NP) to identify geriatric syndromes, set patient/caregiver expectations, assess rehabilitation potential, clarify goals of care, and communicate information directly to SNF providers. Results: The intervention was feasible, addressed unmet needs and errors in the SNF transition process, and was associated with lower 30-day readmission rates compared with concurrent patients not enrolled in the HOPE. Conclusions: An NP-led hospital to SNF transitional care program is a promising means of improving hospital to SNF transitions. Abstract : Supplemental Digital Content is Available in the Text.